A new astrapothere (Mammalia, Meridiungulata) from La Meseta Formation, seymour (Marambio) Island, and a reassessment of previous records of antarctic astrapotheres - Bond, Mariano; Kramarz, Alejandro Gustavo; Macphee, Ross Douglas Earle; Reguero, Marcelo Alfredo (American Museum Novitates)
During the past quarter century, the uplifted nearshore sediments comprising the Eocene La Meseta Formation (LMF) of Seymour (Marambio) Island have produced a diverse assemblage of terrestrial mammals that closely, but not exactly, resembles late Early Eocene faunas from southern Patagonia. This assemblage includes the only astrapothere and litoptern fossils known from outside South America. The occurrence of astrapotheres in LMF was originally indicated by fragmentary dental remains tentatively referred to family Trigonostylopidae on the basis of their general resemblance to the Patagonian genus Trigonostylops Ameghino. In this contribution we describe a new astrapothere specimen from LMF; unlike specimens collected previously, this one is a complete and excellently preserved lower cheek tooth, providing a basis for a review of all previous records of Astrapotheria from this formation. This tooth (probably p4 rather than m1) is sufficiently distinct from all other known astrapothere cheek teeth to warrant assignment to a new genus and species, Antarctodon sobrali. It has a transversally elongated entoconid, resembling that observed in at least one specimen of the Mustersan genus Astraponotus, but the tooth as a whole is much lower crowned and less lophodont than in the latter. Phylogenetic analysis suggests that Antarctodon is closer to genera classified by previous authors as astrapotheriids (e.g., Albertogaudrya and Tetragonostylops) than it is to Trigonostylops. Reexamination of other LMF specimens previously referred to Trigonostylopidae reveals that some specimens are attributable to this new taxon and others either are not astrapotheres at all or lack distinctive features. Consequently, at present the record of order Astrapotheria in Antarctica should be considered as restricted to non-trigonostylopids. Fil: Bond, Mariano. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias ...